Phytochemistry and antifatigue activities of Carica papaya leaf from geothermal, coastal and urban areas, Indonesia - Candra, Aditya; Fahrimal, Yudha; Yusni, Yusni; Azwar, Azwar; Santi, Tahara D. (Narra Sains Indonesia, 2024)
Fatigue, a condition of lack of energy and motivation resulting in the feeling of extreme tiredness or exhaustion, is usually prevented and treated with ergogenic aids, such as in the form of nutritional supplements. Papaya (Carica papaya) may be a potential candidate for ergogenic aids, considering its healthy secondary metabolite properties and number of metabolite compounds that could be affected by the location where the plant growing. The aim of this study was to identify the phytochemicals of papaya leaves from three different locations: geothermal, coastal, and urban areas in Aceh province, Indonesia. Concentrations of papaya leaf with the highest number of secondary metabolite compounds were tested in rats to measure blood lactate acid concentrations after strenuous exercise. The number of chemical compounds identified from the three locations was 24 compounds; 23 compounds and 17 compounds, respectively. The highest concentration of chemical compounds that have antifatigue activity contained in all papaya leaf samples were neophytadiene, linolenic acid, gamma tocopherol, hexadecanoic acid, vitamin E, carpaine, octadecatrienoic acid, nor lean-12-ene, squalene, and phytol. Furthermore, most of the compounds' highest concentrations were found in papaya leaves from the coastal area and, therefore, tested on the animal model. Treatment was provided in 12 male rats with different doses of papaya powder supplements for 15 days. The results showed that lactic acid levels of rats received a dose of 400 mg/kg of papaya leaf extract reduced the lactic acid concentration (p=0.014) compared with the control group. This study highlights that papaya leaves from the coastal area have the most potential activities as ergogenic herbal aid and were able to reduce lactic acid levels in rats after strenuous exercise.